Synthesis and evaluation of 3′-[18F]fluorothymidine-5′-squaryl as a bioisostere of 3′-[18F]fluorothymidine-5′-monophosphate. Issue 20 (29th March 2021) - Brickute, D.; Beckley, A.; Allott, L.; Braga, M.; Barnes, C.; Thorley, K. J.; Aboagye, E. O.
Abstract : [ 18 F]SqFLT was developed to bypass thymidine kinase 1 (TK1) and evaluated for PET imaging of DNA synthesis. Abstract : The squaryl moiety has emerged as an important phosphate bioisostere with reportedly greater cell permeability. It has been used in the synthesis of several therapeutic drug molecules including nucleoside and nucleotide analogues but is yet to be evaluated in the context of positron emission tomography (PET) imaging. We have designed, synthesised and evaluated 3′-[ 18 F]fluorothymidine-5′-squaryl ([ 18 F]SqFLT) as a bioisostere to 3′-[ 18 F]fluorothymidine-5′-monophosphate ([ 18 F]FLTMP) for imaging thymidylate kinase (TMPK) activity. The overall radiochemical yield (RCY) was 6.7 ± 2.5% and radiochemical purity (RCP) was >90%. Biological evaluation in vitro showed low tracer uptake (<0.3% ID mg −1 ) but significantly discriminated between wildtype HCT116 and CRISPR/Cas9 generated TMPK knockdown HCT116 shTMPK− . Evaluation of [ 18 F]SqFLT in HCT116 and HCT116 shTMPK− xenograft mouse models showed statistically significant differences in tumour uptake, but lacked an effective tissue retention mechanism, making the radiotracer in its current form unsuitable for PET imaging of proliferation.